Tunable Elliptic High-pass Filter based on Differentiator Approach - Wongprommoon, Natapong; Pienpichayapong, Peradol; Prommee, Pipat (My University, 2020)
This article presents a design of high-order Elliptic ladder high-pass filter based on differentiators and integrator approach. Since the design of general Elliptic high-pass filter can be realized with high complexity, moreover the high-pass filter held very complicated design. The differentiators and integrator are deployed for synthesis high-pass filter from its Signal Flow Graph (SFG). The Elliptic RLC high-pass filter is transformed by using the original Elliptic RLC low-pass filter. The SFG is straightforward analyzed from the Elliptic RLC high-pass filter prototype. The SFG describes three differentiators and one integrator. The operational transconductance amplifiers (OTA) and grounded capacitors are preferred to implement the differentiators and integrator. The proposed filter contains only 7 OTAs with 4 grounded capacitors. The frequency responses can be varied between 100kHz and 10MHz by manipulating the bias current (IB) from 1μA to 100μA. The performances and the capability are carried out by using PSpice simulation which agreed to the theory.
Keywords: Differentiator; Elliptic; High-pass; OTA